2007
DOI: 10.1007/s00586-007-0444-5
|View full text |Cite
|
Sign up to set email alerts
|

StabilimaxNZ® versus simulated fusion: evaluation of adjacent-level effects

Abstract: Rationale behind motion preservation devices is to eliminate the accelerated adjacent-level effects (ALE) associated with spinal fusion. We evaluated multidirectional flexibilities and ALEs of StabilimaxNZ and simulated fusion applied to a decompressed spine. StabilimaxNZ was applied at L4-L5 after creating a decompression (laminectomy of L4 plus bilateral medial facetectomy at L4-L5). Multidirectional Flexibility and Hybrid tests were performed on six fresh cadaveric human specimens (T12-S1). Decompression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
0
3

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 18 publications
8
21
0
3
Order By: Relevance
“…additional axial preload). However, related to other studies [20,25] the present results indicate that the cosmicMIA system is likely to decrease the ROM in axial rotation to a greater extent than other non-fusion devices. Normalised to the intact state the results in axial rotation for the Dynesys published by Schmoelz et al [25] showed a comparable increase in ROM for the defect model (approximately 220%) and no reduction of the ROM to the range of the intact specimen after instrumentation with the Dynesys.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…additional axial preload). However, related to other studies [20,25] the present results indicate that the cosmicMIA system is likely to decrease the ROM in axial rotation to a greater extent than other non-fusion devices. Normalised to the intact state the results in axial rotation for the Dynesys published by Schmoelz et al [25] showed a comparable increase in ROM for the defect model (approximately 220%) and no reduction of the ROM to the range of the intact specimen after instrumentation with the Dynesys.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, one might speculate that the motion restricting effect of the rigid instrumentation is underestimated. However, the ROM for the rigid instrumentation in the present study is comparable with the ROM reported for rigid instrumentation in the literature [20,25]. Meyers et al evaluated the load sharing in posterior dynamic stabilisation devices using instrumented pedicle screws [17].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Stiffness or hybrid protocols, rather than flexibility protocols, must be used to study the effects of surgical interventions on the biomechanics of the adjacent (non-operated) spinal levels [28,40]. With these methods, segmental kinematics are evaluated for the intact nonfusion, fusion, and TDR situations at an identical spinal posture [14,26,27,29,36,40,41]. However, some of the studies that have been performed to study TDR's adjacent to fusions [10,25,34] did not apply hybrid testing methods [10,34], or applied bending using an offset shear force that resulted in combined bending and shear loading [25].…”
Section: Introductionmentioning
confidence: 99%